INVITRO CYTO TOXICITY OF TRICHODESMA INDIUM LINN.R.BR., EXTRACTS AGAINST THREE HUMAN CANCER CELL LINES. - Mangai, S.Alarmal; Subban, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective:Trichodesma Indicum Linn.R.Br. of Boraginaceae family was traditionally used as an anticancer plant material. The present study was aimed to evaluate the cytotoxic activity of the plant against three human cancer cell lines-Breast cancer cell line (MCF-7), Cervical cancer cell line (HeLa) and laryngeal epithelial carcinoma cell line(HEp2),since a few clinical trials are needed to confirm its anticancer activity. Method: The chloroform& ethanol extracts of the plant were used for in-vitro screening. The cytotoxic effect of the plant was analysed by MTT assay. Results: The results obtained are statistically analysed by one way analysis of Variance(ANOVA)and it was found that the ethanol extract has stronger cytotoxic activity than chloroform extract against all the tested cell lines. However higher degree of cyto toxicity was found to be in ethanol extract against human breast cell line (MCF-7) (IC50 57.41µg/ml). Conclusion: The traditional use of the plant material as anticancer was correlated with its invitro cyto toxicity results. The plant has a remarkable cytotoxic activity against the tested cancer cell lines. Keywords: Boraginaceae, Cytotoxic activity, IC50 value, MTT assay, Trichodesma Indicum